2022
DOI: 10.1111/tmi.13784
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of an exercise‐based cardiovascular rehabilitation program in patients with chronic Chagas cardiomyopathy in Brazil: An analysis from the PEACH study

Abstract: Objectives: The present study aimed to perform a cost-effectiveness analysis of an exercise-based cardiovascular rehabilitation (CR) program in patients with chronic Chagas cardiomyopathy (CCC). Methods: Cost-effectiveness analysis alongside a randomised clinical trial evaluating the effects of a 6-month exercise-based CR program. The intervention group underwent 3 weekly exercise sessions. The variation of peak oxygen consumption (VO 2peak ) was used as a measurement of clinical outcome. Cost information from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Given that EBTP offers a different and potentially more cost-effective alternative compared to conventional treatments, it is worth considering. Studies such as PEACH, which evaluated the cost-effectiveness of an exercise-based cardiovascular rehabilitation program in patients with CCC in Brazil, have demonstrated that EBTP can be a cost-effective tool to improve patients' condition [41] . Furthermore, the implementation of home-based cardiac rehabilitation (EBTP at home) has been associated with better outcomes, including improvements in health-related quality of life and physical fitness, compared to conventional, center-based cardiac rehabilitation (EBTP at healthcare centers).…”
Section: Discussionmentioning
confidence: 99%
“…Given that EBTP offers a different and potentially more cost-effective alternative compared to conventional treatments, it is worth considering. Studies such as PEACH, which evaluated the cost-effectiveness of an exercise-based cardiovascular rehabilitation program in patients with CCC in Brazil, have demonstrated that EBTP can be a cost-effective tool to improve patients' condition [41] . Furthermore, the implementation of home-based cardiac rehabilitation (EBTP at home) has been associated with better outcomes, including improvements in health-related quality of life and physical fitness, compared to conventional, center-based cardiac rehabilitation (EBTP at healthcare centers).…”
Section: Discussionmentioning
confidence: 99%